ANALISIS FUNGSI INTERMEDIASI DAN RISIKO KREDIT MACET (STUDI KASUS PERBANDINGAN BANK UMUM DAN BPR) DI PROVINSI BALI - Desak Ayu Sriary Bhegawati (Faculty of Economics and Business, Universitas Warmadewa, 2018)
The development of economy indonesian does not get separated from the role of the government, in the financial sector institutions, and the business operators.Monetary wisdom as one part of this superior wisdom have an important role in meeting of the bank in realizing an objective of national development.Economic development in a country very much dependent on the development of dynamic and real contribution of the country banking sector. Bank is a a financial institution that has a duty as an intermediary finances between the sides parties who have these surplus funds with the party who deficit of funds.Intermediation function run by banking institutions participate as an agent in the accelerated development and to increase economic growth and become better at public welfare.Naturally bank able to perform intermediation function with a deal with different types of borrowers and regulatory framework institutional and appropriate, banks have better preparations in the face of asymetric information.Non performing loan is the ratio use for measures the bank in managing risk repayment failure by the debtor.The lower the percentage of Non Performing Loan, then the bank will experience advantage, but if the percentage of non performing loan of the increasing, the banks will be a loss.Intermediation function (Loan to Depocit Ratio) there are differences between commercial banks (Loan to Depocit Ratio) and BPR (Loan to Depocit Ratio) in bali, this indicates of Public Credit Bank more capable of carries on the intermediation function. The Public Credit Bank better able to intermediation function.The value of Non Performing Loans to outstanding loans Commercial Bank and Public Credit Bank in bali there was a gap in it is seen of the value Non Performing Loans to outstanding loans Public Credit Bank higher than the commercial, as by Loan to Depocit Ratio of higher Public Credit Bank than the Commercial Bank. Keywords : Commercial Bank, Public Credit Bank, Loan to Deposit Ratio,and Non Performing Loans